2016
DOI: 10.21010/ajtcam.v13i4.18
|View full text |Cite
|
Sign up to set email alerts
|

Hexane Extract of Dacryodes Edulis Fruits Possesses Anti-Diabetic and Hypolipidaemic Potentials in Alloxan Diabetes of Rats.

Abstract: Background: The fruit extract of Dacryodes edulis (D. edulis), the African pear or plum, a tree indigenous to the humid tropics has been used for managing wounds, skin diseases, sickle cell anaemia, dysentery and fever in some African nations. In South Eastern Nigeria, 'herbal doctors' include its marshed fruit in decoctions administered to diabetic patients. However no scientific substantiation of their claim and use exist in literature. Hence, the need to evaluate the antidiabetic and hypolipidaemic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
1
7
1
Order By: Relevance
“…These findings concur with those obtained by Aristimunha et al (2016) and Ogbe and Affiku (2012) . Proportionately, the amounts determined from different plant parts in this study (see Table 2 ) compare well with those reported in other studies evaluating D. edulis phytochemical composition ( Ogboru, 2015 ; Ebana et al, 2016 ; Okolo et al, 2016 ; Oyetunji and Opeyemi, 2017 ). These compounds have been noted to possess bactericidal, virucidal, fungicidal, and antiparasitical properties which can be exploited in pharmaceutical medicine or animal feed additives.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings concur with those obtained by Aristimunha et al (2016) and Ogbe and Affiku (2012) . Proportionately, the amounts determined from different plant parts in this study (see Table 2 ) compare well with those reported in other studies evaluating D. edulis phytochemical composition ( Ogboru, 2015 ; Ebana et al, 2016 ; Okolo et al, 2016 ; Oyetunji and Opeyemi, 2017 ). These compounds have been noted to possess bactericidal, virucidal, fungicidal, and antiparasitical properties which can be exploited in pharmaceutical medicine or animal feed additives.…”
Section: Discussionsupporting
confidence: 89%
“…There exists little information on the plant use in managing animal diseases and correcting nutritional deficiencies in Africa and its use in treating human ailments ( Ebana et al, 2016 ) and its reported nutritional characteristics ( Vidanarachchi et al, 2005 ) informed its choice in this study. Determination of product efficacy and safety is the first step in considering its use in animal feed or human food chain ( Okolo et al, 2016 ). A phytochemical analysis is a good starting point in testing the efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the LD 50 was greater than 5000 mg/kgbw and this classifies the extract as relatively non-toxic according to Hodger and Sterners's toxicity scale [ 26 ]. There is a dearth of literature on the acute toxicity of Dacryodes edulis leave - extracts till date; however, a recent study by Okolo et al [ 27 ] have reported an LD 50 of 3500 mg/kgbw for n-hexane extract of fruits of Dacryodes edulis ; which is at variance with this present study. The observed difference in LD 50 of the two studies could be because the two studies investigated two different parts of the plant (fruit and leaves) using different solvents/extraction procedures.…”
Section: Discussioncontrasting
confidence: 83%
“…Oral acute doses of hexane extract reduced level of blood glucose whereas, sub‐chronic administration of the hexane extract significantly improved the conditions of hyperglycaemia, total cholesterol, triglycerides, and reduced the level of LDL‐C, ALT and ALP, but significantly enhanced the level of HDL‐C. Pancreatic tissues after sub‐chronic administration demonstrated that both glibenclamide and extract (1,600 mg/kg) restored the architecture of damaged pancreatic β‐cell using histopathological analysis (Okolo et al, 2016).…”
Section: Pharmacological Activities Of Plant‐based Extracts and Compomentioning
confidence: 99%